Virulence-related protein synthesis in Naegleria fowleri. - Hu, W N (1991)
Protein synthesis patterns of the low-virulence Naegleria fowleri LEE strain from axenic culture, the same strain after mouse brain passage to increase virulence, and the same strain after growth on bacteria were studied. Comparisons of accumulated proteins, in vivo-synthesized proteins, and in vitro-synthesized proteins translated from poly(A)+ mRNA were made. Differences between amoebae from the different treatments were noted. After 6 months in axenic culture, pathogenic protein synthesis patterns were lost and there was a decrease in virulence. Therefore, the increase in virulence is correlated with numerous specific changes in protein synthesis.